"I Definitely Would Appreciate a Little More Validation": Toward an Ethics of Care in College Newsrooms and Journalism Education. (June 2023) - Arrey, Taylor; Reynolds, Chelsea
Drawing on interviews with 10 U.S. student journalists, we introduce an ethics-of-care approach for trauma-informed journalism pedagogy. We express grave concern for mental health in journalism programs, offering an empirical snapshot of students' traumas and coping strategies. We confirm that student journalists, like working reporters, are traumatized by professional norms, high demands, poor boundaries, safety concerns, and ethical-professional responsibilities. Participants coped through emotional distancing, saving face, and relying on peers. We offer interventions based on student support needs and changing news values, including faculty affirmation, financial support, counselor support, diversity training, newsroom debriefings, emotional leadership, and reporting protocols.